Volume 1: Symposia, Parts a and B 2012
DOI: 10.1115/fedsm2012-72108
|View full text |Cite
|
Sign up to set email alerts
|

Flow Visualization Using Cavitation Within Blade Passage of an Axial Waterjet Pump Rotor

Abstract: Cavitation phenomena within an axial waterjet pump, AxWJ-2 [1,2] operating at and below the best efficiency point (BEP) are investigated using high-speed imaging. The purpose of these preliminary observations is to provide an overview of the physical appearance of several forms of cavitation under varying flow and pressure conditions. These observations provide a motivation for upcoming detailed velocity and turbulence measurements. The experiment is conducted using a transparent pump installed in an optically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Yoon et al (2006) demonstrated that tip vortex becomes strengthened and migrates upstream as the flow coefficient decreases, which was also validated by Tan et al (2014) found that the evolution of TLV becomes more abrupt, in terms of the initial location and breakdown process near the pre-stall condition. Furthermore, using high-speed imaging, Tan et al (2012) also discovered that the sheet cavitation is thin at BEP condition, while it becomes thickened as a result of an increase in the incidence angle of the flow entering the passage relative to the blade. Fig.6a shows hydraulic performance of the pump model with 3 blades (BEP is under rated condition).…”
Section: Effect Of Flow Coefficientmentioning
confidence: 98%
“…Yoon et al (2006) demonstrated that tip vortex becomes strengthened and migrates upstream as the flow coefficient decreases, which was also validated by Tan et al (2014) found that the evolution of TLV becomes more abrupt, in terms of the initial location and breakdown process near the pre-stall condition. Furthermore, using high-speed imaging, Tan et al (2012) also discovered that the sheet cavitation is thin at BEP condition, while it becomes thickened as a result of an increase in the incidence angle of the flow entering the passage relative to the blade. Fig.6a shows hydraulic performance of the pump model with 3 blades (BEP is under rated condition).…”
Section: Effect Of Flow Coefficientmentioning
confidence: 98%
“…Moreover, it becomes thicker due to the increase in incidence angle. 3 In contrast, the cloud cavity is eventually separated at the impeller shroud along the streamwise direction. [4][5][6][7] The cloud cavity is complex owing to the flow rates and blade geometries.…”
Section: Introductionmentioning
confidence: 99%
“…The three-dimensional structure and the evolution of TLV have been recently documented using high-speed imaging [20][21][22]. Figure 10a presents the major vortex structure from 33% chord to 67% chord, illustrating that the TLV gradually moves away from the blade along the blade chord.…”
Section: Three Dimensional Structure and Evolution Of Tlvmentioning
confidence: 99%
“…This paper provides an indepth survey of the TLV structure and evolution in different perspectives. From a twodimensional perspective, Miorini, Wu, and Tan [16][17][18][19][20][21][22] systemically investigated the inner structure and turbulent evolution of TLV using PIV and high-speed imaging. For example, they conducted PIV measurements at several chord sections to observe the flow structure in an axial water-jet pump (see Figures 8 and 9).…”
Section: Two-dimensional Structure and Evolution Of Tip-leakage Vortementioning
confidence: 99%
See 1 more Smart Citation